Tin-plated steel sheet and can

By forming a leather film containing tin oxides and tin sulfide on the surface of tin -plated steel plates, the problem of decreased resistance to tin -plated steel plates in existing technologies can be used without chromate treatment. Yellow -resistant degeneration.

CN119384525APending Publication Date: 2025-01-28NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380046718.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Without chromate treatment, it is difficult to effectively inhibit the sulfide blackening and the growth of tin oxides, resulting in a decrease in resistance.

Method used

By generating the leather membrane containing sulfide and tin sulfide on the surface of the tin -plated steel plate, optimize the adhesion of the tin -tin layer and the composition of the cortex layer, forming a layer or decentralized sulfide and tin sulfide structure.

Benefits of technology

In the case of not being treated with chromate, it significantly improves the sulfurization black degeneration and yellow -resistant degeneration of tin -plated steel plates, and improves its corrosion resistance and appearance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384525A_ABST
    Figure CN119384525A_ABST
Patent Text Reader

Abstract

Provided is a tin-plated steel sheet for containers, said steel sheet having a zirconium-containing coating layer, without having to undergo conventional chromate treatment. The tin-plated steel sheet has further excellent yellowing resistance. A tin-plated steel sheet having: a steel sheet; a tin plating layer on at least one surface of the steel sheet; and a coating layer that is positioned on the tin plating layer and contains zirconium oxide and tin sulfide, the amount of tin plating layer deposited in the coating layer being 0.1 g / m2 to 15 g / m2 in terms of the amount of metal Sn, the amount of zirconium oxide deposited in the coating layer being 0.2 mg / m2 to 50 mg / m2 in terms of the amount of metal Zr, and the amount of tin sulfide deposited in the coating layer being 0.1 mg / m2 to 5 mg / m2 in terms of the amount of sulfur.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a tin-plated steel sheet and a can.

[0002] This application claims priority based on Japanese Patent Application No. 2022-098082 filed in Japan on June 17, 2022, and the contents are incorporated herein by reference. Background Art

[0003] Tinplate is commonly known as "tinplate" and is widely used in cans for holding beverages or food and other food-related uses. This is because tin is safe for the human body and is an aesthetically pleasing metal.

[0004] The tin-plated steel sheet is mainly manufactured by electroplating. This is because the electroplating method is advantageous over the hot-dip method in order to control the amount of tin, a relatively expensive metal, to the minimum necessary amount. That is, the tin-plated steel sheet is manufactured by performing an electroplating treatment, or an electroplating treatment and a heating and melting treatment, thereby forming a tin plating layer with a beautiful metallic luster on the surface of the steel sheet. Furthermore, in most cases, a chromate film is applied to the tin-plated layer of the tin-plated steel sheet by performing a chromate treatment such as an electrolytic treatment using a hexavalent chromate solution or an immersion treatment.

[0005] The effects of the chromate film include preventing the tin plating from being sulfidized and blackened, preventing the tin plating from being yellowed, and preventing the deterioration of the coating film adhesion. The sulfidized and blackened tin plating is a phenomenon in which the S (sulfur) in the contents of the can reacts with the tin (Sn) and iron (Fe) contained in the tin plating to generate black sulfides. The sulfidized and blackened tin plating can be prevented by forming a chromate film. In addition, the yellowing of the tin plating is a phenomenon caused by the progress of oxidation on the surface of the tin plating. The yellowing of the tin plating can be suppressed by forming a chromate film. Furthermore, the deterioration of the coating film adhesion is a phenomenon caused by the cohesion failure of tin oxide when the tin plating is applied for use. The deterioration of the coating film adhesion can be prevented by forming a chromate film between the tin plating and the coating film.

[0006] On the other hand, in recent years, due to the increasing awareness of the environment and safety, it is required that the final product does not contain hexavalent chromium, and further, it is required that the chromate treatment itself is not performed. However, as mentioned above, the tin-plated steel sheet without the formation of a chromate film has a reduced resistance to sulfide blackening, a yellowing of the appearance due to the growth of tin oxides, and a reduced coating film adhesion.

[0007] Therefore, several tin-plated steel sheets subjected to coating treatment instead of chromate coating have been proposed.

[0008] For example, Patent Document 1 below proposes a tin-plated steel sheet in which a film containing P and Si is formed by treating the tin-plated steel sheet with a solution containing phosphate ions and a silane coupling agent.

[0009] Furthermore, Patent Document 2 below proposes a tin-plated steel sheet which is treated with a solution containing aluminum phosphate to form a film containing a reaction product of Al and P, at least one of Ni, Co, and Cu, and a silane coupling agent.

[0010] Furthermore, Patent Document 3 below proposes a method for producing a tin-plated steel sheet having no chromate film, wherein Zn is plated on a tin plated layer and then a heat treatment is performed until the Zn plated layer disappears.

[0011] Furthermore, Patent Documents 4 and 5 below propose a steel sheet for a container having a chemical conversion treatment film containing zirconium, phosphoric acid, a phenolic resin, and the like.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Publication No. 2004-60052

[0015] Patent Document 2: Japanese Patent Application Publication No. 2011-174172

[0016] Patent Document 3: Japanese Patent Application Laid-Open No. 63-290292

[0017] Patent Document 4: Japanese Patent Application Publication No. 2007-284789

[0018] Patent Document 5: Japanese Patent Application Publication No. 2010-13728 Summary of the invention

[0019] Problems to be solved by the invention

[0020] However, the tin-plated steel sheets and the methods for producing the same proposed in Patent Documents 1 to 5 cannot sufficiently suppress the generation of black sulfides and the growth of tin oxides over time, and have problems such as poor resistance to blackening due to sulfidation and poor resistance to yellowing.

[0021] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a tin-plated steel sheet and a can having further excellent resistance to sulfur blackening and yellowing without performing conventional chromate treatment.

[0022] Means for solving problems

[0023] The inventors of the present invention have conducted intensive studies to solve the above problems and have found that a tin-plated steel sheet having even better yellowing resistance can be realized without chromate treatment by forming a film containing zirconium oxide and tin sulfide on the surface of the tin-plated steel sheet.

[0024] The gist of the present invention completed based on the above findings is as follows.

[0025] (1) A tin-plated steel sheet, characterized in that it has:

[0026] Steel plates;

[0027] a tin-based plating layer located on at least one surface of the steel sheet; and

[0028] A film layer located on the tin-based plating layer and containing zirconium oxide and tin sulfide,

[0029] The adhesion amount of the above tin-based plating layer is 0.1 g / m 2 ~15g / m 2 ,

[0030] The amount of zirconium oxide deposited in the film layer was 0.2 mg / m 2 ~50 mg / m 2 The adhesion amount of the above tin sulfide is 0.1 mg / m 2 ~5 mg / m 2 .

[0031] (2) The tin-plated steel sheet according to (1), characterized in that the tin sulfide is SnS.

[0032] (3) A can made of the tin-plated steel sheet described in (1) or (2) above.

[0033] The tin sulfide is preferably present in a layered form on the surface of the film layer.

[0034] Furthermore, it is preferred that the tin sulfide is dispersedly present inside the film layer.

[0035] Furthermore, it is preferred that the tin sulfide is dispersed inside the film layer and exists in a layered form on the surface of the film layer.

[0036] Effects of the Invention

[0037] According to the present invention, it is possible to provide a tin-plated steel sheet and a can which are further excellent in resistance to sulfur blackening and yellowing without performing conventional chromate treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1It is a schematic cross-sectional view of a tin-plated steel sheet as an embodiment of the present invention, and is a schematic view of a case where zirconium oxide and tin sulfide are formed in a layered state.

[0039] Figure 2 It is a schematic cross-sectional view of a tin-plated steel sheet as an embodiment of the present invention, and is a schematic view of a case where zirconium oxide and tin sulfide are mixed and formed.

[0040] Figure 3 It is a schematic cross-sectional view of a tin-plated steel sheet as an embodiment of the present invention, and is a schematic view of a case where zirconium oxide and tin sulfide are mixed and tin sulfide is formed in a layered state.

[0041] Figure 4 It is a perspective view showing an example of a tank as an embodiment of the present invention. DETAILED DESCRIPTION

[0042] Hereinafter, preferred embodiments of the present invention will be described in detail.

[0043] The present invention described below relates to tinplate steel sheets widely used for cans for containing food, beverages, etc. More specifically, it relates to tinplate steel sheets and cans having further excellent resistance to sulfur blackening and yellowing without conventional chromate treatment.

[0044] <1.Tin-plated steel sheet>

[0045] The tin-plated steel sheet of this embodiment is characterized in that Figure 1 to Figure 3 As shown in , it comprises: a steel sheet; a tin-based plating layer provided on at least one surface of the steel sheet; and a film layer provided on the surface of the tin-based plating layer and containing a predetermined amount of zirconium oxide and tin sulfide.

[0046] (1.1 Steel Plate)

[0047] The steel plate used as the base material of the tin-plated steel sheet of the present embodiment is not particularly limited, and any steel plate can be used as long as it is a steel plate used in general tin-plated steel sheets for containers. Examples of such steel plates include low-carbon steel plates, ultra-low-carbon steel plates, and the like.

[0048] (1.2 Tin plating)

[0049] Tin plating is performed on at least one or both sides of the steel sheet as described above to form a tin-based plating layer. The tin-based plating layer improves the corrosion resistance of the steel sheet. It should be noted that the "tin-based plating layer" in this specification includes not only a plating layer formed of metallic tin, but also a plating layer in which impurities are mixed in metallic tin and a plating layer containing trace elements in metallic tin.

[0050] That is, the tin-based plating layer contains 90.0% by mass or more of tin (Sn) and the remaining impurities. In addition, the tin-based plating layer may also be formed by 90.0% by mass or more of tin (Sn) and the remaining impurities. The content of tin contained in the tin-based plating layer in this case may also be 95.0% by mass or more, 98.0% or more, 99.0% or more, 99.5% or more, or 99.9% or more. Furthermore, in addition to tin and impurities, trace amounts of alloying elements may also be included.

[0051] In addition, the tin-based plating layer may also contain more than 50.0% by mass of tin (Sn), 0 to 20% by mass of Fe and the remaining impurities. In addition, the tin-based plating layer may also be formed by more than 50.0% by mass of tin (Sn), 0 to 20% by mass of Fe and the remaining impurities. Furthermore, in addition to tin, Fe and impurities, trace amounts of alloying elements may also be included. The tin-based plating layer containing tin and Fe is composed of an Fe-tin alloy. In addition, the tin-based plating layer may be a single-layer structure of an Fe-tin alloy layer, or a two-layer structure of an Fe-tin alloy layer and a tin layer stacked on the Fe-tin alloy layer. In this case, the ratio of the thickness of the tin layer to the iron-tin alloy layer is not particularly limited.

[0052] As described above, the tin-based plating layer can take various forms, but as long as the adhesion amount in terms of the amount of metallic tin described below is ensured in the entire tin-based plating layer, the chemical composition of the tin-based plating layer is not necessarily limited in the present invention.

[0053] In the tin-based plating of the present embodiment, the amount of the tin-based plating applied per single surface is not particularly limited, but can be set to 0.1 g / m2, for example, in terms of the amount of metallic tin. 2 ~15g / m 2 , preferably set to 1.0g / m 2 ~10g / m 2 The amount of tin plating applied to each side is 0.1 g / m2 in terms of tin conversion. 2 In the above case, the corrosion resistance can be made sufficiently excellent. In addition, the adhesion amount per single side of the tin-based plating layer is 15 g / m 2 In the following cases, the decrease in adhesion and the increase in cost can be suppressed, and the effect of improving the corrosion resistance brought by tin can be fully obtained. The lower limit of the amount of tin-based plating per single side is preferably 1.0 g / m 2 More preferably, 2.0 g / m 2 Above, 2.5g / m 2 The upper limit of the amount of tin-based plating per single surface is preferably 10 g / m 2 Below, more preferably 5.0 g / m 2Below, 4.0g / m 2 Below, 3.5g / m 2 Below, 3.0g / m 2 the following.

[0054] Here, the above-mentioned tin adhesion amount per single side is set to a value measured by the electrolytic stripping method or fluorescent X-ray analysis method described in JIS G 3303: 2017, for example. In the case of measuring by fluorescent X-ray analysis, the fluorescent X-ray used in the measurement is set to the original ray of SnαK (wavelength of 0.0492nm). Rh is used as the target of the X-ray tube, and the tube voltage and tube current are set to appropriate values ​​in the range of 30 to 40 kV and 80 to 100 mA, respectively. The slit width, the spectroscopic crystal, and the detector select conditions suitable for the resolution of the measured fluorescent X-ray and the range of tin adhesion amount. In addition, a standard line is made by the intensity of fluorescent X-rays from a test piece with a known amount of tin adhesion. Then, the tin-based plating of the measurement object is irradiated with X-rays under the set conditions, and the intensity of fluorescent X-rays is measured. Next, the amount of tin adhesion in the tin-based plating is obtained from the intensity of fluorescent X-rays through the standard line. The measurement site was set to a circular area with a diameter of 30 mm on the surface of the membrane layer, and the measurement was performed at 5 arbitrary measurement sites on the surface of the membrane layer, and the arithmetic mean value was used as the measurement result.

[0055] When measuring the amount of tin deposited in the tin-based plating layer, it is not necessary to remove the film layer, and the amount of tin deposited can be measured directly from the surface of the film layer using fluorescent X-rays while the film layer is still present.

[0056] In order to determine the amount of iron in the tin-based plating layer (the amount of iron in the tin-iron alloy layer), an electrolytic stripping method (constant current electrolysis method) is used. Specifically, the following method is used. After cutting the tin-plated steel sheet into a test piece of 20 mm × 50 mm in size, 4 cm of the surface 2 The portion outside the measurement area, that is, the portion outside the measurement area in the above surface and the portion including the entire surface on the opposite side of the above surface were sealed with tape and immersed in 1 mol / L, 150 mL, 25°C hydrochloric acid, with the counter electrode set to a Pt plate and the reference electrode set to a silver / silver chloride electrode (saturated with KCl) for 4 cm 2An anodic current of 0.02A is passed through the tin-plated steel sheet, and the tin-based plating layer is dissolved while the potential at this time is measured. In the time region from the start of the measurement, the potential of the tin-plated steel sheet relative to the silver / silver chloride electrode (saturated KCl) is such that the region (A) below -0.4V is the time region where non-alloyed tin is detected, the region (B) above -0.4V and below -0.3V is the time region where the tin plating layer containing iron (tin-iron alloy layer) is detected, and the region above -0.3V is the time region where the portion of the steel sheet that becomes the base is detected. The length of region (B) (time T(B) (seconds)) is measured, and the amount of tin that becomes the tin-iron alloy layer (g / m 2 ).

[0057] Tin content (g / m 2 )={118.7×0.02×T(B) / (96500×2)}×2500

[0058] The amount of iron in the plating layer is calculated from the amount of tin by the following formula.

[0059] Iron content (g / m 2 )=[tin amount]×55.85 / 293.25

[0060] The above measurement was performed on five random locations of the tin-based plating layer, and the arithmetic average thereof was taken as the iron content.

[0061] (1.3 Film layer containing zirconium oxide and tin sulfide)

[0062] The tin-plated steel sheet of the present embodiment has a film layer containing zirconium oxide and tin sulfide on the surface of the steel sheet having the tin-based coating as described above. It should be noted that, in the film layer, as long as the effect of the present invention is not hindered, substances other than zirconium oxide and tin sulfide, such as compounds containing P (phosphorus) and compounds containing F (fluorine) may also be included. In addition, the content of organic components in the film layer is preferably less than 0.1% by mass. In the present embodiment, organic components such as polymer compounds and organic compounds are not intentionally added components, but may be inevitably contained as long as the effect of the present invention is not hindered. The film layer may contain various substances in addition to zirconium oxide and tin sulfide as described above, but as long as the Zr adhesion amount and sulfur amount described below are ensured in the entire film layer, the limitation of the components of the film layer in the present invention is not necessary.

[0063] By forming the above-mentioned zirconium oxide and tin sulfide on the surface of the tin-plated steel sheet, the yellowing resistance can be further improved. The reason is not clear, but the inventors of the present invention have conducted detailed investigations and believe that it is as follows.

[0064] In the past, for example, a film containing zirconium oxide, such as that shown in Patent Document 4 or Patent Document 5, was formed on the surface of the tin-plated layer by utilizing the increase in pH due to the generation of hydrogen from the surface of the tin-plated layer caused by cathode electrolysis. However, the film containing zirconium oxide formed by this method is in a relatively rough state, so oxygen easily permeates, and the surface of the tin-plated layer is easily oxidized and yellowed. In addition, the film containing zirconium oxide contains a trace amount of tin, which also causes yellowing due to oxidation of the tin.

[0065] Therefore, the inventors of the present invention tried to improve the yellowing resistance of the conventional film containing zirconium oxide, and found that by forming a film containing zirconium oxide and tin sulfide on a tin-plated steel sheet, the growth of tin oxide can be suppressed, thereby improving the yellowing resistance. This is presumed to be due to: (A) the excellent barrier property of tin sulfide itself to oxygen permeation; and (B) the coexistence of zirconium oxide and tin sulfide increases the density of the film, thereby improving the barrier property to oxygen permeation.

[0066] The amount of zirconium oxide deposited is required to be 0.2 mg / m 2 ~50 mg / m 2 . Below 0.2mg / m 2 In the case of sulfur black degeneration resistance is poor, more than 50mg / m 2 The preferred range is 0.5 mg / m 2 ~25 mg / m 2 The more preferred range is 1.0 mg / m 2 ~10 mg / m 2 .

[0067] Regarding the above-mentioned amount of Zr deposited, a value obtained by performing fluorescent X-ray measurement on a tin-plated steel sheet having a coating layer according to the present embodiment formed on the surface thereof was defined as the amount of Zr deposited.

[0068] There is no problem even if zirconium oxide contains any element such as Fe, Ni, Cr, Ca, P, Na, Mg, Al, Si, P, F, etc. The zirconium oxide containing these elements may be, for example, a composite oxide containing zirconium as a main component.

[0069] That is, zirconium oxide is a substance represented by the chemical formula of zirconium and oxygen as the main body, for example, ZrO2. In addition, P or F may be dissolved in zirconium oxide, or P or F may be contained in a form of substitution with a part of oxygen. Furthermore, Fe, Ni, Cr, Ca, P, Na, Mg, Al, and Si may be dissolved in or substituted as described above. The presence of zirconium oxide can be confirmed by the following method: When the film layer is subjected to X-ray photoelectron spectroscopy (XPS), Zr3d appears in the range of 182.3±0.5eV. 5 / 2 In addition, P and F may be contained in the film while being contained in the zirconium oxide.

[0070] The composition of the tin sulfide is not particularly limited, but examples thereof include SnS, SnS2, and Sn2S3. The amount of tin sulfide deposited needs to be 0.1 mg / m3 in terms of sulfur. 2 ~5 mg / m 2 . In terms of sulfur content, it is less than 0.1 mg / m 2 In the case of sulfur content exceeding 5 mg / m 2 In the case of excessive amounts, the appearance will change due to the color of the tin sulfide itself, which is not preferred. For example, since SnS is grayish black and SnS2 and Sn2S3 are yellow, if the amount is excessive, the appearance will be black or yellow. The more preferred range is 0.2 mg / m 2 ~3 mg / m 2 In addition, from the viewpoint of improving yellowing resistance, as the tin sulfide, SnS which does not have a yellowish color of the tin sulfide itself, such as SnS2 and Sn2S3, is preferred.

[0071] In addition, about the sulfur content, the value obtained from the result of fluorescent X-ray measurement was made into the sulfur content by the tin-plated steel sheet which has the film layer of this embodiment formed on the surface.

[0072] When measuring the amount of Zr and sulfur in the film layer by fluorescent X-ray analysis, the fluorescent X-rays used in the measurement are set to the original rays of ZrαK (wavelength of 0.0787nm) and SαK (wavelength of 0.537nm). Rh is used as the target of the X-ray tube, and the tube voltage and tube current are set to appropriate values ​​in the range of 30-40kV and 80-100mA, respectively. The slit width, the spectroscopic crystal, and the detector are selected to be suitable for the resolution of the measured fluorescent X-rays, the range of the amount of Zr and the amount of sulfur. In addition, a standard line is prepared by the intensity of fluorescent X-rays from the test pieces with known amounts of Zr and sulfur. Then, the film layer of the measurement object is irradiated with X-rays under the set conditions, and the intensity of fluorescent X-rays is measured. Next, the amount of Zr and the amount of sulfur in the film layer are calculated from the intensity of fluorescent X-rays through the standard line. The measurement site was set to a circular area with a diameter of 30 mm on the surface of the membrane layer, and the measurement was performed at 5 arbitrary measurement sites on the surface of the membrane layer, and the arithmetic mean value was used as the measurement result.

[0073] It should be noted that the above-mentioned film layer containing zirconium oxide and tin sulfide can also be Figure 1 As shown in , the two are formed in layers as a membrane layer. Figure 1 In the example shown in , a layer containing zirconium oxide is provided on the tin-based plating layer, and a layer containing tin sulfide is provided on the tin-based plating layer.

[0074] In addition, the membrane layer can also be Figure 2 As shown in the figure, it is a layer in which zirconium oxide and tin sulfide are dispersed and mixed. Figure 2 In the example shown in , zirconium oxide constitutes a matrix of the film layer, and tin sulfide is dispersed in the matrix.

[0075] Furthermore, the membrane layer can also be Figure 3 As shown in , zirconium oxide and tin sulfide are dispersed and mixed, and a layer containing tin sulfide is formed on the surface side of the film layer. Figure 3 In the example shown in , zirconium oxide constitutes a matrix of the film layer, tin sulfide is dispersed in the matrix, and a layer containing tin sulfide exists in the surface layer.

[0076] In this embodiment, if Figure 1 , Figure 2 and Figure 3 As shown in , regardless of the state of zirconium oxide and tin sulfide, the resistance to sulfide blackening and yellowing can be improved. Figure 1In the case of the form shown in , by the presence of layered tin sulfide on the surface side of the film layer, for example, when the tin-plated steel sheet of this embodiment is used as a structural material for a can, even if sulfur (S) is generated by the food filled in the can, the layered tin sulfide acts as a barrier, and the layer formed by the zirconium oxide also has a barrier effect on the invasion of sulfur (S), so sulfur cannot invade the tin-based plating side, and the generation of new tin sulfide can be suppressed, thereby improving the resistance to sulfide blackening.

[0077] In addition, Figure 2 In the case of the form shown in , zirconium oxide and tin sulfide exist inside the film layer. Therefore, for example, even if cracks are generated in the film layer when the tin-plated steel sheet of this embodiment is formed into a can, and sulfur (S) is generated by the food filled in the can while the cracks remain, almost all of the tin (Sn) contained in the film layer is converted into tin sulfide. Therefore, further generation of tin sulfide can be suppressed, thereby improving resistance to sulfide blackening.

[0078] Furthermore, in Figure 3 In the case of the form shown in Figure 1 and Figure 2 Therefore, even if sulfur (S) is generated from the food stored in the can, the generation of new tin sulfides can be suppressed, thereby improving the resistance to sulfur blackening.

[0079] In addition, Figures 1 to 3 In any of the embodiments, since the tin-based plating layer is covered with the film layer, the generation of tin oxides on the surface of the tin-based plating layer can be suppressed, thereby improving the yellowing resistance.

[0080] In order to confirm that the film layer of this embodiment is Figure 1 to Figure 3 Which form of the tin-plated steel sheet is, can be confirmed by observation under a transmission electron microscope. Specifically, a thin film sample of the film layer is prepared by a slicing method in such a way that the cross section of the tin-plated steel sheet of the present embodiment can be observed. In a 100nm×100nm area of ​​the obtained thin film sample (an area where the film thickness is 100nm in a direction parallel to the width of the sheet and 100nm in the thickness direction of the sheet), a 200kV field emission transmission electron microscope (FE-TEM) is used to observe at least 5 areas at a magnification of 1 million times, and an energy dispersive X-ray analyzer (EDS) is used for element mapping. The existence areas of Sn, Zr, and S are confirmed by the element mapping results. When Sn and S are detected at the same position, tin sulfide exists at that position. In addition, zirconium oxide exists in the area where Zr is detected. By operating in this way, by confirming the existence positions of tin sulfide and zirconium oxide, it can be confirmed that Figure 1 to Figure 3 Which form of .

[0081] It should be noted that, in the case where the plate width direction of the film sample cannot be clearly determined, it can be determined as follows. The plate width direction of the film sample is the plate width direction of the steel plate before the film sample is made, and is a direction orthogonal to the rolling direction and the plate thickness direction. The so-called rolling direction refers to the direction parallel to the elongation direction of the grains in the metal structure of the steel plate. The so-called elongation direction of the grains refers to the direction parallel to the long axis direction of the grains. The long axis direction of all the grains may not be completely in the same direction, and there may be some unevenness. Therefore, for example, by image analysis of an electron microscope, 5 grains are arbitrarily selected, the long axis direction of each grain is obtained, and the unit vectors of each long axis direction are obtained. The sum of each unit vector is used as a composite vector, and the direction of the composite vector is used as the long axis direction of the grain, and the direction parallel to it is used as the rolling direction.

[0082] In addition, the tin-plated steel sheet of the present embodiment only needs to have a tin-based plating layer and a film layer on at least one surface of the steel sheet. On the other surface of the steel sheet, either or both of the tin-based plating layer and the film layer may be present, or both of the tin-based plating layer and the film layer may not be present. In addition, the tin-plated steel sheet may also have a tin-based plating layer and a film layer on both surfaces of the steel sheet. In addition, the tin-plated steel sheet of the present embodiment may also have a layer or a film composed of other components on the other surface.

[0083] <2.Can>

[0084] As an example, the tin-plated steel sheet of this embodiment can be used as a raw material for cans. Figure 4 In the embodiment, as an example of a can, a DR can that can be used to store food is illustrated. The can made of the tin-plated steel sheet of the present embodiment as a raw material can be used as a food can or a beverage can, as well as an oil or paint can, etc., and its use is not particularly limited. The manufacturing method of the can is not particularly limited, and can be a general method. For example, if it is a three-piece can, the can body is manufactured in the following manner: after the tin-plated steel sheet of the present embodiment is cut into a prescribed shape, the cut tin-plated steel sheet is rounded into a cylindrical shape and the two ends are welded. In addition, the bottom cover and the top cover are manufactured by punching the tin-plated steel sheet into a prescribed shape. Then, by rolling and joining any one of the bottom cover and the top cover with the can body, after filling the contents such as food, any other of the bottom cover and the top cover with the can body is rolled and joined, thereby manufacturing a can containing food. At this time, the membrane part of the present embodiment is configured at least on the inner surface side of the can body, the bottom cover and the top cover. Of course, the film portion of this embodiment may be further arranged on the outer surface side.

[0085] Since the can of the present embodiment is made of the tin-plated steel sheet of the present embodiment, and the tin-plated steel sheet is excellent in resistance to blackening and yellowing due to sulfurization, concerns about food hygiene can be reduced.

[0086] The tin-plated steel sheet of the present embodiment can be produced by any method, and can be produced, for example, by the method for producing a tin-plated steel sheet described below.

[0087] <3. Method for manufacturing tin-plated steel sheet>

[0088] An example of a method for manufacturing a tin-plated steel sheet according to the present embodiment is described. The method for manufacturing a tin-plated steel sheet according to the present embodiment is manufactured by immersing a steel sheet having a tin-based plating layer on at least one side in a solution containing zirconium ions or performing a first cathode electrolysis treatment in a solution containing zirconium ions, thereby generating zirconium oxide on the tin-based plating layer, and then performing a second cathode electrolysis treatment on the steel sheet after the zirconium oxide is formed in an electrolyte solution containing sulfur (S).

[0089] It should be noted that in the present embodiment, before the first and second cathode electrolytic treatments, a steel sheet is prepared, and a tin-based plating layer is formed on at least one surface of the steel sheet by tin plating.

[0090] (3.1 Preparation of steel plate)

[0091] First, a steel plate that will be the base material of the tin-plated steel plate is prepared. The manufacturing method and material of the steel plate used are not particularly specified, and examples thereof include steel plates manufactured through processes such as casting, hot rolling, pickling, cold rolling, annealing, and temper rolling. The annealing process may be continuous annealing or intermittent box annealing.

[0092] (3.2 Formation of tin-based plating)

[0093] Next, a tin-based plating layer is formed on at least one surface of the steel sheet. The method for applying the tin-based plating layer on the steel sheet surface is not particularly specified, but for example, a known electroplating method is preferred, and a hot dip plating method in which the steel sheet is immersed in molten tin for plating may also be used.

[0094] As the electroplating method, for example, an electrolytic method using a well-known Ferrostan bath, a halogen bath, an alkaline bath, etc. can be utilized. It should be noted that, as required, before forming the tin-based plating layer, the steel plate can also be subjected to a cleaning treatment such as degreasing and pickling. The method is not limited, as long as it is a method that can remove oil, oxides, and other foreign matter on the surface of the steel plate. For example, chemical treatments such as degreasing and subsequent pickling, shot blasting, sand blasting, particle blasting, and dry ice spraying can be cited. There is no problem in combining these chemical treatments and mechanical treatments.

[0095] For degreasing, for example, a sodium hydroxide aqueous solution with a concentration of 10 to 50 g / L can be used at 20 to 80°C and a current density of 5 to 40 A / dm 2Perform cathodic electrolytic degreasing or anodic electrolytic degreasing for 0.2 to 5 seconds.

[0096] In pickling, in addition to pickling treatment without electrolysis and only immersing the steel plate, there are no restrictions on the method such as cathode electrolytic pickling and anodic electrolytic pickling, which have a strong cleaning effect on the surface of the steel plate. In industrial production, cathode electrolytic pickling is a general and preferred method because it has a strong cleaning effect on the surface of the steel plate and is not easy to cause over-pickling. For example, it can be applied in a pickling bath with a sulfuric acid concentration of 5 to 40% and a temperature of 30 to 90°C with a current of 5 to 50C / dm 2 Cathodic electrolytic pickling is carried out.

[0097] The method for applying the tin-based plating layer on the steel sheet surface is not particularly specified, but a known electroplating method is preferred. As the electroplating method, for example, a known electrolytic method using an acid bath such as a sulfuric acid bath, a boron fluoride bath, a phenolsulfonic acid bath, a methanesulfonic acid bath, or an alkaline bath can be used.

[0098] Alternatively, a hot-dip plating method may be used in which a tin-based plating layer is formed by immersing a steel sheet in a molten Sn plating bath.

[0099] It should be noted that after tin plating, a heat melting treatment may be performed by heating the steel sheet to the melting point of tin, i.e., 231.9° C. or higher. This heat melting treatment can provide gloss on the surface of the tin-plated steel sheet, and generate an alloy layer of tin and Fe, i.e., an iron-tin alloy layer, between the tin-plated layer and the steel sheet, thereby further improving corrosion resistance.

[0100] (3.3 Cathode electrolysis treatment)

[0101] Hereinafter, a method for forming a film layer containing zirconium oxide and tin sulfide according to the present embodiment will be described.

[0102] [First cathode electrolysis treatment]

[0103] In order to produce the coating layer of the present embodiment, first, a coating film containing zirconium oxide is formed on the tin-based plating layer formed on the steel sheet.

[0104] The film containing zirconium oxide can be formed on the tin-plated layer by immersing the tin-plated steel sheet in a solution containing zirconium ions or subjecting the tin-plated steel sheet to a first cathode electrolytic treatment in a solution containing zirconium ions.

[0105] It should be noted that, in addition to the cathode electrolysis treatment, the film can also be formed by immersion treatment. However, in the immersion treatment, the surface of the tin-based plating layer is etched to form a film containing zirconium oxide, so the amount of adhesion tends to become uneven, and the treatment time also becomes longer, so it is disadvantageous in industrial production compared with the cathode electrolysis treatment.

[0106] In the cathode electrolysis treatment, the surface cleaning brought about by the forced charge transfer and the generation of hydrogen at the interface between the tin plating layer and the electrolyte is also coordinated with the adhesion promotion effect brought about by the increase in pH, so that a uniform film can be obtained. Furthermore, in the first cathode electrolysis treatment, by the coexistence of nitrate ions and ammonium ions in the treatment solution, a short-time treatment of several seconds to tens of seconds can be achieved, which is extremely advantageous in industry. Therefore, for the generation of the zirconium oxide-containing film of the present embodiment, it is preferred to use a method based on cathode electrolysis.

[0107] The concentration of zirconium ions in the solution (hereinafter referred to as cathode electrolyte) for implementing the first cathode electrolysis treatment can be appropriately adjusted according to the production equipment and production speed (capacity), but for example, the zirconium ion concentration is preferably 100ppm to 4000ppm. In addition, there is no problem in including other components such as fluoride ions, ammonium ions, nitrate ions, sulfate ions, and phosphate ions in the cathode electrolyte containing zirconium ions.

[0108] Here, the liquid temperature of the cathode electrolyte is not particularly specified, but is preferably set in the range of 10°C to 50°C, for example. By performing cathode electrolysis at a temperature below 50°C, a dense and uniform film structure formed by very fine particles can be generated. In addition, by setting the liquid temperature of the cathode electrolyte to below 50°C, the generation of defects, cracks, microcracks, etc. in the structure of the generated zirconium oxide film can be prevented, and the reduction of the adhesion of the coating film can be prevented. In addition, by setting the liquid temperature of the cathode electrolyte to above 10°C, the efficiency of film generation can be improved, and even when the outside temperature is high, the solution does not need to be cooled, which is economical.

[0109] In addition, the pH of the cathode electrolyte is not particularly specified, but is preferably 3.0 to 5.0. If the pH is 3.0 or more, the production efficiency of zirconium oxide can be improved, and if the pH is 5.0 or less, a large amount of precipitation of, for example, zirconium hydroxide in the cathode electrolyte can be prevented, and continuous productivity can be improved.

[0110] It should be noted that, in order to adjust the pH of the cathode electrolyte and improve the electrolysis efficiency, for example, nitric acid, ammonia water, etc. may be added to the cathode electrolyte.

[0111] In addition, the current density during cathode electrolysis is preferably set to, for example, 0.05 A / dm 2 ~50A / dm 2 At a current density of 0.05A / dm 2In the above case, the production efficiency of zirconium oxide can be sufficiently improved, a stable film layer containing zirconium oxide can be produced, and the resistance to sulfur blackening and yellowing can be sufficiently excellent. 2 In the case of the following conditions, the generation efficiency of zirconium oxide can be made appropriate, and the generation of coarse zirconium oxide with poor adhesion can be suppressed. A more preferred current density range is 1 A / dm 2 ~10A / dm 2 .

[0112] It should be noted that when forming a film containing zirconium oxide, the time of cathode electrolysis may be appropriately adjusted according to the current density with respect to the target Zr deposition amount. Specifically, the time of cathode electrolysis may be set within the range of 0.4 to 5 seconds.

[0113] As the solvent of the solution used for cathode electrolysis, for example, distilled water can be used, but the solvent is not limited to water such as distilled water, and can be appropriately selected according to the material to be dissolved, the production method, and the like.

[0114] The zirconium in the cathode electrolysis can be supplied from a zirconium complex such as H2ZrF6. The Zr in the Zr complex is converted into Zr by the increase of pH at the cathode electrode interface. 4+ The Zr ions are further reacted in the cathode electrolyte to form zirconium oxide. When phosphoric acid is contained in the electrolyte, zirconium phosphate is also generated.

[0115] In addition, as the energization mode during cathode electrolysis, either continuous energization or intermittent energization may be used without any problem.

[0116] During cathode electrolysis, the relative flow rate of the cathode electrolyte and the steel plate is preferably set to 50 m / min or more. If the relative flow rate is 50 m / min or more, it is easy to make the pH of the steel plate surface accompanied by hydrogen generation when power is turned on uniform, and the generation of coarse zirconium oxide can be suppressed. It should be noted that the upper limit of the relative flow rate is not particularly specified. In addition, the relative flow rate of the cathode electrolyte and the steel plate is the speed difference between the flow rate of the cathode electrolyte and the speed of the steel plate passing through the plate. In the case where the cathode electrolyte is a static bath, that is, the relative flow rate of the cathode electrolyte is 0 m / min, it becomes the speed of the steel plate passing through the plate.

[0117] [Second cathode electrolysis treatment]

[0118] The film layer containing zirconium oxide and tin sulfide of the present embodiment can be obtained by further subjecting the steel sheet having the film containing zirconium oxide formed on the tin-based plating layer to a second cathode electrolysis treatment in an electrolyte solution containing sulfur. The electrolyte solution used is not particularly specified with respect to specific components, but for example, a sodium thiosulfate aqueous solution containing sodium thiosulfate as an electrolyte can be cited.

[0119] The concentration of sodium thiosulfate is not particularly limited, but is preferably set to 10 to 40 g / L as sodium thiosulfate. The electrolysis conditions are also not particularly limited, but are preferably set to a solution temperature of 30 to 60° C. and a current of 0.5 to 10 C / dm 2 As long as the above-mentioned current range is met, there is no special requirement for the current value and electrolysis time. As more preferred conditions, the sodium thiosulfate concentration is 20 to 30 g / L, the solution temperature is 40 to 50°C, and the current is 1 to 5 C / dm 2 If it is within these ranges, tin sulfide can be formed efficiently, and it is also suitable in industry. It should be noted that the Sn source of the tin sulfide formed in the second cathode electrolytic treatment is Sn contained in the tin-based plating layer.

[0120] As the solvent of the solution used in cathode electrolysis, distilled water can be used, but it is not limited to water such as distilled water. In addition, as the energization mode during cathode electrolysis, it can be continuous energization or intermittent energization, and there is no problem.

[0121] It should be noted that by appropriately adjusting the conditions of the second cathode electrolysis treatment represented by the electrolysis time, the membrane layer can be separated into Figure 1 to Figure 3 The form shown in .

[0122] By setting the concentration of sodium thiosulfate in the solution, the temperature of the solution and the amount of electricity supplied to the above ranges, and further setting the electrolysis time to less than 2.0 seconds, it is possible to form Figure 2 The film layer in which zirconium oxide and tin sulfide are dispersed and mixed as shown in FIG. It is presumed that this is because: since the electrolysis time is as short as 2.0 seconds or less, the amount of tin sulfide precipitated is relatively small, and tin sulfide is mainly generated inside the film layer, thereby obtaining a film layer in which zirconium oxide and tin sulfide are dispersed and mixed. It should be noted that in order to make the adhesion amount of tin sulfide sufficient, the lower limit of the electrolysis time is preferably set to 0.4 seconds or more.

[0123] In addition, by setting the concentration of sodium thiosulfate in the solution, the temperature of the solution and the amount of electricity supplied to the above ranges, and further setting the electrolysis time to more than 2.0 seconds, it is possible to form Figure 3As shown in , a film layer in which zirconium oxide and tin sulfide are dispersed and mixed, and a layer of tin sulfide is formed on the surface side. It is presumed that this is because, since the electrolysis time is as long as more than 2.0 seconds, tin sulfide is generated not only inside the film layer but also on the surface of the film layer, thereby obtaining a film layer in which zirconium oxide and tin sulfide are dispersed and mixed in the film layer and a layer of tin sulfide is formed on the surface. It should be noted that in order to prevent the adhesion amount of tin sulfide from becoming excessive, the upper limit of the electrolysis time is preferably set to 10 seconds or less.

[0124] Furthermore, by setting the concentration of sodium thiosulfate in the solution to a high concentration of 55 to 70 g / L, setting the temperature and current flow of the solution to the above range, and setting the electrolysis time to 0.8 seconds or less in this state, it is possible to form Figure 1 The film layer is formed by laminating a layer composed of zirconium oxide and a layer composed of tin sulfide as shown in . It is presumed that this is because by setting the concentration of sodium thiosulfate to a high concentration and setting the electrolysis time to 0.8 seconds or less, tin sulfide is generated only on the surface of the film layer, thereby obtaining a film layer formed by laminating a layer composed of zirconium oxide and a layer composed of tin sulfide. In order to make the adhesion amount of tin sulfide sufficient, the lower limit of the electrolysis time is preferably set to 0.4 seconds or more.

[0125] Through the above, the tin-plated steel sheet of this embodiment can be manufactured.

[0126] Example

[0127] Next, the tin-plated steel sheet and the method for manufacturing the tin-plated steel sheet of the present invention are specifically described while showing the embodiments and comparative examples. It should be noted that the embodiments shown below are only examples of the tin-plated steel sheet and the method for manufacturing the tin-plated steel sheet of the present invention, and the tin-plated steel sheet and the method for manufacturing the tin-plated steel sheet of the present invention are not limited to the following examples.

[0128] <Test Materials>

[0129] For the low-carbon cold-rolled steel sheet with a thickness of 0.2 mm, as a pretreatment, electrolytic alkaline degreasing, water washing, dilute sulfuric acid electrolytic pickling, water washing, electroplating tin using a phenolsulfonic acid bath, and then heating and melting treatment are performed. The adhesion amount of the tin plating layer is about 2.8 g / m per single side in terms of the amount of metallic tin. 2 As a benchmark, but some test materials change the amount of tin plating by changing the power-on time. In addition, test materials that are not heated and melted after electroplating are also made. The example of no heating and melting is No.A18 in Table 1 (B18 in Table 2). The amount of tin plating is determined by measuring using a fluorescent X-ray method (ZSX Primus made by Rigaku Corporation). The measurement conditions are set as described above.

[0130] The steel sheet having the tin-plated layer produced as described above was subjected to cathodic electrolysis in an aqueous solution containing zirconium fluoride (first cathodic electrolysis treatment) to form a zirconium oxide layer on the tin-plated layer. The current density, flow rate, pH, and bath temperature were appropriately changed.

[0131] Furthermore, the tin-plated steel sheet on which the zirconium oxide layer was formed was subjected to cathode electrolysis in a 5 to 70 g / L sodium thiosulfate aqueous solution (second cathode electrolysis treatment) to generate tin sulfide. The bath temperature was set at 20 to 65°C, and the amount of electricity for cathode electrolysis was set at 0 to 15 C / dm 2 It should be noted that No. a1 in Table 1 (No. b1 in Table 2) was not subjected to cathode electrolysis but was treated by immersion.

[0132] Table 1 shows the conditions of the first cathode electrolysis treatment and the second cathode electrolysis treatment.

[0133] [Table 1]

[0134]

[0135] The underlined portion indicates that the conditions are outside the range of the preferred production conditions.

[0136] Cathodic electrolytic treatment 2 of No. a1 was set as an immersion treatment in a sodium thiosulfate solution for 2 seconds. The tin-plated steel sheets produced as described above were subjected to various evaluations shown below.

[0137] [Attachment amount]

[0138] The amount of Zr deposited and the amount of sulfur per single surface were determined by a fluorescent X-ray method (ZSX Primus manufactured by Rigaku Corporation). The measurement conditions were set as described above.

[0139] [Structure of tin sulfide]

[0140] The Sn3d 5 / 2 and S2p 3 / 2 The peak position of the bonding energy of Sn3d was investigated. When determining the peak position, the overall spectrum was shifted so that the peak position of carbon (C1s) detected on the surface of the sample became 284.8 eV, and on this basis, the peak position of Sn3d was calculated. 5 / 2 and S2p 3 / 2 The bonding energy position.

[0141] In Sn3d 5 / 2 The peak position of S2p satisfies the range of 485.4 to 485.9 eV, and 3 / 2When the peak position of satisfies the range of 160.1 to 163.9 eV, it is determined to be SnS.

[0142] In addition, in Sn3d 5 / 2 The peak position of S2p satisfies the range of more than 485.9 and less than 486.4 eV, and 3 / 2 When the peak position of satisfies the range of 160.1 to 163.9 eV, it is judged to be Sn2S3.

[0143] Furthermore, in Sn3d 5 / 2 The peak position of S2p satisfies the range of more than 486.4 and less than 487.9 eV, and 3 / 2 When the peak position of satisfies the range of 160.1 to 163.9 eV, it is judged to be SnS2.

[0144] [Yellowing resistance]

[0145] The tin-plated steel sheets prepared by the method described in the above <Test Materials> were subjected to a wet test in a constant temperature and humidity chamber maintained at 40°C and 80% relative humidity for 4 weeks, and the color difference b before and after the wet test was obtained. * The change in value △b * , evaluate yellowing resistance.

[0146] △b * The value of 1 or less was considered excellent (E), the value of more than 1 and less than 2 was considered very good (VG), the value of more than 2 and less than 3 was good (G), and the value of more than 3 was poor (P), and the evaluations E, VG, and G were set as pass. * The value of b is less than 2, but before the wet test (initial) * When the value is 6 or more, it is also set to evaluation G.

[0147] It should be noted that b * The value was measured using a commercially available colorimeter, SC-GV5 manufactured by Suga Test Instruments. * The measurement conditions are: light source C, total reflection, and a measurement diameter of 30 mm.

[0148] [Coating film adhesion]

[0149] The coating film adhesion was evaluated in the following manner.

[0150] The tin-plated steel sheets prepared by the method described in the above <Test Materials> were subjected to a wet test by the method described in [Yellowing Resistance], and 7 g / m2 of tin-plated steel sheets were coated on the surface in terms of dry weight. 2A commercially available epoxy resin paint for cans was baked at 200°C for 10 minutes and left at room temperature for 24 hours to form a coating film. Afterwards, a cross-cut test was performed on the tin-plated steel sheet with the coating film formed thereon. In the cross-cut test, a grid pattern cut was formed on the coating film, reaching the surface of the steel sheet, and an adhesive tape was pasted on the grid pattern portion. The adhesive tape was peeled off within 5 minutes to evaluate the peeling state of the coating film. The grid pattern cut was formed in the following manner: using a cutting tool with a blade, 7 linear scars were produced in the longitudinal and transverse directions at intervals of 3 mm. The relative angle of the longitudinal and transverse cuts was set to 90°.

[0151] After the tape was peeled off, the case where the coating film (test surface) in the grid pattern area (test surface) was not peeled off at all was evaluated as excellent (E), the case where less than 10 area% of the coating film on the test surface was peeled off was evaluated as very good (VG), the case where more than 10 area% and less than 20 area% of the coating film on the test surface was peeled off was evaluated as good (G), and the case where more than 20 area% of the coating film on the test surface was peeled off was evaluated as poor (P). The evaluations E, VG, and G were set as qualified, and P was set as unqualified.

[0152] [Resistance to black sulphur denaturation]

[0153] The resistance to sulfur black discoloration was evaluated in the following manner.

[0154] The surface of the tin-plated steel sheet produced by the method described in the above [Yellowing Resistance] and wet tested was coated with 7 g / m2 of tin-plated steel sheet in terms of dry weight. 2 After applying a commercially available epoxy resin paint for cans, the coated steel sheet was baked at 200°C for 10 minutes and left at room temperature for 24 hours to form a coating film. After that, the tin-plated steel sheet with the coated steel sheet was cut into a predetermined size, immersed in an aqueous solution containing 0.3% sodium dihydrogen phosphate, 0.7% sodium hydrogen phosphate, and 0.6% L-cysteine ​​hydrochloride, respectively, and subjected to a distillation treatment at 121°C / 60 minutes in a sealed container. The appearance after the distillation treatment was evaluated.

[0155] The case where no black discoloration was observed on the test surface before and after the test was evaluated as excellent (E), the case where black discoloration was observed in an area less than 5% of the test surface was evaluated as very good (VG), the case where black discoloration was observed in an area greater than 5% and less than 10% of the test surface was evaluated as good (G), and the case where black discoloration was observed in an area greater than 10% of the test surface was evaluated as poor (P). Evaluations E, VG, and G were set as passed, and P was set as failed.

[0156] [Corrosion resistance after painting]

[0157] The corrosion resistance after coating was evaluated in the following manner.

[0158] The surface of the tin-plated steel sheet produced by the method described in the above [Yellowing Resistance] and wet tested was coated with 7 g / m2 of tin-plated steel sheet in terms of dry weight. 2 After applying a commercially available epoxy resin coating on cans, the coating was formed by baking at 200°C for 10 minutes and leaving it at room temperature for 24 hours. After that, the tin-plated steel sheet after the coating was formed was cut into a predetermined size and visually evaluated for the presence or absence of rust after being immersed in commercially available tomato juice at 60°C for 7 days.

[0159] The case where no rust was confirmed was evaluated as excellent (E), the case where rust was confirmed in an area less than 5% of the test surface was evaluated as very good (VG), and the case where rust was confirmed in an area exceeding 5% of the test surface was evaluated as poor (P). Evaluations E and G were set as pass, and P was set as fail.

[0160] Table 2 shows the results of investigation of the amount of tin deposited in the tin-based plating layer, the amount of zirconium deposited in the film layer, the amount of sulfur deposited, and the structure and various properties of tin sulfides of the tin-plated steel sheet obtained under the production conditions of Table 1.

[0161] As shown in Table 2, all of B1 to B23, which are within the range of the present invention, have good performance. In particular, the zirconium deposition amount is 1.0 to 10 mg / m 2 , and the sulfur adhesion is 0.2 to 3 mg / m 2 , and the performance of any of B16, B17, B19 to B21, in which the structure of tin sulfide is SnS, is particularly excellent.

[0162] Furthermore, observations using a transmission electron microscope revealed that the morphology of the membranes of B1 to 18 was Figure 2 The morphology of the membranes of B19 to B21 is shown in Figure 3 The morphology of the membranes of B22 and B23 is shown in Figure 1 The form shown in .

[0163] On the other hand, Comparative Examples b1 to b18, in which at least any one of the zirconium deposition amount and the sulfur deposition amount was out of the range of the present invention, were found to be inferior in yellowing resistance, coating film adhesion, sulfur blackening resistance, and corrosion resistance after painting.

[0164] b1 has a small amount of Sn deposited on the tin-based plating layer, and the current in the second cathode electrolysis treatment is set to 0 C / dm 2 , an immersion treatment was performed instead of the second cathode electrolytic treatment 2. Therefore, SnS was not precipitated in the film layer, and yellowing resistance, coating adhesion, sulfur blackening resistance, and corrosion resistance after coating became insufficient.

[0165] In b2, the zirconium ion concentration in the first cathode electrolytic treatment was low, the amount of metal Zr in the film layer decreased, and the yellowing resistance, sulfide blackening resistance, and corrosion resistance after painting became insufficient.

[0166] In b3, the zirconium ion concentration in the first cathode electrolytic treatment was excessive, the amount of metal Zr in the film layer became excessive, and the coating adhesion became insufficient.

[0167] In b4, the liquid temperature in the first cathode electrolytic treatment was low, the amount of metal Zr in the film layer decreased, and the yellowing resistance, sulfide blackening resistance, and corrosion resistance after painting became insufficient.

[0168] In b5, the liquid temperature in the first cathode electrolytic treatment was high, the amount of metal Zr in the film layer became excessive, and the yellowing resistance and coating adhesion became insufficient.

[0169] The pH in the first cathode electrolytic treatment of b6 was low, the amount of metal Zr in the film layer decreased, and the yellowing resistance, sulfide blackening resistance, and corrosion resistance after painting became insufficient.

[0170] In b7, the pH in the first cathode electrolytic treatment was high, the amount of metal Zr in the film layer became excessive, and the coating adhesion became insufficient.

[0171] The current density in the first cathode electrolysis treatment of b8 was low, the amount of metal Zr in the film layer decreased, and the yellowing resistance, sulfide blackening resistance, and corrosion resistance after painting became insufficient.

[0172] The current density in the first cathode electrolysis treatment of b9 was high, the amount of metal Zr in the film layer became excessive, and the coating adhesion became insufficient.

[0173] In b10, the relative flow rate in the first cathode electrolytic treatment was low, the amount of metal Zr in the film layer decreased, and the amount of S also decreased, resulting in insufficient yellowing resistance, black sulfide discoloration resistance, and corrosion resistance after painting.

[0174] In b11, the sodium thiosulfate concentration in the second cathode electrolytic treatment was low, the amount of S in the film layer decreased, and the yellowing resistance, sulfur blackening resistance, and corrosion resistance after painting became insufficient.

[0175] b12 Since the sodium thiosulfate concentration in the second cathode electrolysis treatment exceeds 40 g / L and the power-on time is 2 seconds, the S amount in the film layer becomes excessive and the resistance to sulfur black degeneration becomes insufficient.

[0176] In b13, the liquid temperature in the second cathode electrolytic treatment was low, the amount of S in the film layer decreased, and the yellowing resistance, sulfide blackening resistance, and corrosion resistance after painting became insufficient.

[0177] In b14, the liquid temperature in the second cathode electrolysis treatment was high, the amount of S in the film layer became excessive, and the resistance to black sulfide degeneration became insufficient.

[0178] In b15, the amount of current applied in the second cathode electrolytic treatment was low, the amount of S in the film layer decreased, and the yellowing resistance, sulfur blackening resistance, and corrosion resistance after painting became insufficient.

[0179] In b16, the amount of current in the second cathode electrolysis treatment was high, the amount of S in the film layer became excessive, and the resistance to black sulfide degeneration became insufficient.

[0180] Since b17 and b18 did not undergo the first cathode electrolytic treatment, the amount of zirconium oxide deposited in the film layer was 0 mg / m 2 in terms of the amount of metal Zr, and the resistance to black sulfide degeneration and corrosion resistance after painting were insufficient.

[0181] [Table 2]

[0182]

[0183] The underlined part indicates that it is outside the scope of the present invention.

[0184] Industrial Applicability

[0185] According to the present invention, a tin-plated steel sheet having further excellent resistance to sulfur blackening and yellowing can be provided without performing conventional chromate treatment, and thus has industrial applicability.

Claims

1. A tin-plated steel sheet, characterized in that: It has: Steel plates; a tin-based plating layer located on at least one surface of the steel sheet; and a film layer located on the tin-based plating layer and containing zirconium oxide and tin sulfide, The adhesion amount of the tin-based plating layer is 0.1 g / m 2 ~15g / m 2 , The amount of zirconium oxide deposited in the film layer was 0.2 mg / m 2 ~50 mg / m 2 The adhesion amount of the tin sulfide is 0.1 mg / m 2 ~5 mg / m 2 .

2. The tin-plated steel sheet according to claim 1, characterized in that: The tin sulfide is SnS.

3. A can made of the tin-plated steel sheet according to claim 1 or claim 2.

Citation Information

Patent Citations

  • Production of thinly tinned steel sheet having superior rust resistance and weldability

    JP1988290292A

  • METHOD FOR PRODUCING TINNED STEEL SHEET HAVING Si-CONTAINING CHEMICAL CONVERSION FILM

    JP2004060052A

  • Steel sheet for container having excellent can-making workability

    JP2007284789A

  • Steel sheet for container which has excellent organic coating film performance, and method of manufacturing the same

    JP2010013728A

  • Tinned steel sheet and method for producing the same

    JP2011174172A